2017
DOI: 10.1093/omcr/omx055
|View full text |Cite
|
Sign up to set email alerts
|

Calcific uremic arteriolopathy

Abstract: Calcific uremic arteriolopathy (CUA) or Calciphylaxis is a rare disease typically seen in end stage renal disease patients on dialysis and is associated with high mortality rates, mainly because of sepsis. Medial calcification of the dermal arterioles is the characteristic histologic finding together with vascular thrombosis and ischemic necrosis. CUA involves legs, abdomen and gluteal region in majority of the patients. Herein, we present a case of CUA of the glans penis in a uremic patient. Unfortunately, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The authors also reported that STS possesses vasodilatory and antioxidant properties. Their findings were in agreement with previous reports that suggested that STS could combine with insoluble tissue calcium salts to form calcium thiosulfate, a salt that can later be dialyzed [ 11 , 58 , 59 , 60 ]. Thus, treatment of calciphylaxis with STS is partly due to its antioxidant and calcium-chelating and vasodilatory properties.…”
Section: Clinical Usefulness Of Stssupporting
confidence: 92%
See 1 more Smart Citation
“…The authors also reported that STS possesses vasodilatory and antioxidant properties. Their findings were in agreement with previous reports that suggested that STS could combine with insoluble tissue calcium salts to form calcium thiosulfate, a salt that can later be dialyzed [ 11 , 58 , 59 , 60 ]. Thus, treatment of calciphylaxis with STS is partly due to its antioxidant and calcium-chelating and vasodilatory properties.…”
Section: Clinical Usefulness Of Stssupporting
confidence: 92%
“…In a recent experimental rat model of hyperoxaluria and renal injury, 0.4 g/kg dose of STS treatment scavenged reactive oxygen species (ROS) in a dose-dependent manner, mitigated cellular hydrogen peroxide levels, and maintained superoxide dismutase activity [ 6 ]. It is important to note that thiosulfate has two lone electron pairs: one at the single bonded sulfur moiety of the disulfide bond and the other at the single bonded oxygen [ 60 ]. This characteristic allows thiosulfate to act as an effective antioxidant by donating electrons to unpaired damaging electrons associated with mitochondrial ROS [ 37 , 63 , 64 ].…”
Section: Potential Clinical Applications Of Stsmentioning
confidence: 99%
“…A total of 50 cases of penile calciphylaxis have been reported in the English literature ( Table 1 ) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The average age was 54.5 years (range 32 to 81).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to passive calcium deposition in degenerative tissue, active ossification is seen in vascular calcification in the form of endochondral and intramembranous (non-endochondral) ossifications [6]. Calcific uremic arteriolopathy is another form of calcification seen in hemodialysis [7]. It is hypothesized that vascular smooth muscle responds to the increase of serum phosphate by mineralizing it with calcium in the extracellular matrix.…”
Section: Pathogenesis and Pathophysiologymentioning
confidence: 99%